INTEGRATED ENTREPRENEURSHIP MODEL FOR TOURISM - Szczepanowski, Adam (Acta Scientiarum Polonorum. Oeconomia, 2010)
Tourism which constitutes an essential factor of economic development of many places and regions does not develop to a large extent in Polish voivodeships having the highest natural potential (on the basis of CSO data in recent years). Therefore, there is a need for increasing tourism competitiveness in these regions. The author in the study places a thesis, that entrepreneurship growth of tourist sector is an essential factor, raising and strengthening competitiveness of Polish tourism and Polish economy in Europe. The first part of the study introduces an issue and most important features of entrepreneurship. The second part is dedicated to discussion of an integrated entrepreneurship model for tourism, based on entry and exit factors including the idea of sustainable development.